Constraints in Adoption of Climate Resilient Technologies in Rainfed Agro-Ecosystem - Jasna V. K. , R. Roy Burman , R. N. Padaria , J. P. Sharma , Eldho Varghese , Bidisha Chakrabarty, N. Loganandhan and Sanjay Kumar, (Indian Journal of Extension Education, 2016)
Climate change and food security are the two daunting present day agrarian challenges. Adaptation through climateresilience is an undebatably accepted solution to better respond to these challenges. National Innovations in ClimateResilient Agriculture (NICRA) is an Indian Council of Agricultural Research (ICAR) initiative launched with a focus onmaking most vulnerable districts of the nation climate resilient. Since the inception of the project, a number of climateresilient technologies have been demonstrated across the country. The present investigation was undertaken with anobjective to isolate the constraints in adoption of these technologies in rainfed agro-ecosystem. The results showedthatOfficials evaluated technical constraints, and labour and economic constraints as the most severe than that by thefarmers.Among different technical factors, 'inadequacy of inputs' stood first with mean rank 3.87 in hindering adoption asregarded by the farmers. But officials considered 'poor availability and accessibility of short duration drought tolerantcrop varieties' as the most severe one (mean rank is 3.3). Among labour and economic constraints, 'longer gestation period(mean ran k=3.74) to get the returns from adopted intervention' and 'shortage of owned resources'(mean rank =3.95) weremajor constraints as per the opinion of farmers and officials, respectively. 'Resistance to change the conventionalpractices' was considered as the most severe by both farmers(mean rank =3.99) and officials (mean rank = 4.05) in socialand personal constraints. The findings will help in redesigning the already implemented interventions to ensure a higheradoption by managing the constraints.